The Assessment of Usability and Service Quality in E-Commerce Using the Integration of Analytical Hierarchy Process (AHP) and Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) - Alfian Abdul Ghaffar; Indrawati (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: This study aims to identify evaluation criteria for e-commerce platforms and determine the top-performing platform in the Indonesian marketplace. Design/Methodology/Approach: The research employs a quantitative approach, utilising the Analytical Hierarchy Process (AHP) and the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) model analysis. It involves analysing data from 100 respondents who are users of Shopee, Tokopedia, and Bukalapak e-commerce platforms. Research findings: The findings suggest that the Usability criterion outperforms E-ServQual in terms of scores. Based on the AHP and TOPSIS techniques, Tokopedia, Shopee, and Bukalapak are ranked as the top three e-commerce platforms. Theoretical contribution/Originality: This study contributes to understanding the importance of usability in evaluating e-commerce platforms and provides insights into customer preferences. It also demonstrates the sequential integration of AHP and TOPSIS techniques for evaluating multiple criteria. Practitioner/Policy implications: This study reveals that Satisfaction, Efficiency, and Learnability are crucial sub-criteria for customers when selecting an e-commerce platform. Improving these aspects can enhance consumer purchasing power and improve the overall user experience. Research limitation/Implications: The limitation of the study is its geographic scope, as it was conducted solely in the Jakarta and Yogyakarta regions. Additionally, the research exclusively employs the AHP (Analytical Hierarchy Process) and TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) methods.